Pengaruh Pelayanan dan Komunikasi Terhadap Kepuasan Pasien Rawat Jalan di RS Prima Pekanbaru - Barza, Panzi; Putri, Syiva Septwo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study was to determine the effect of service and communication on outpatient satisfaction at Peima Pekanbaru Hospital. The sample in this study was 100 outpatients at Prima Pekanbaru Hospital. While the variables studied in this study were service, communication and patient satisfaction. Data analysis used multiple linear regression methods using validity tests, reliability tests, normality tests, t tests, f tests and R2 tests. The test was carried out to determine the relationship between the independent variables (independent variables) and the dependent variables (dependent variables). Based on the results of the study, service and communication simultaneously affect patient satisfaction with a correlation value of R = 0.384, which indicates a close relationship between service and communication with outpatient satisfaction at Prima Hospital. While the Adjusted R square is 0.130, which means that service and communication have a contribution of 13% to outpatient satisfaction at Prima Hospital Pekanbaru. Simultaneously, service and communication variables affect outpatient satisfaction at Prima Hospital Pekanbaru with a calculated F value of 8.401 3.94. Partially, it is obtained that the service variable affects outpatient satisfaction at Prima Hospital Pekanbaru with a calculated t value of 2.423 t table 1.985 and the communication variable affects outpatient satisfaction at Prima Hospital Pekanbaru with a calculated t value of 2.158 t table 1.985, the multiple linear regression equation is as follows: Y = 8.456 + 0.117 X1 + 0.154 X2.